Power Dynamics in Supreme Court Oral Arguments: The Relationship between Gender and Justice-to-Justice Interruptions. (3rd July 2019) - Feldman, Adam; Gill, Rebecca D.
Abstract: We examine how gendered norms of professional speech affect the ability of female Supreme Court justices to exercise power in oral argument. In this unique dialogue setting, the justices vie for chances to speak. We argue that gender is an embedded characteristic of oral arguments, and implicit assumptions about gender roles lead to disparities in the balance of authority on the Court. Our results show that women are interrupted more than men, which compromises their ability to achieve their goals during oral arguments. This inequity is compounded by the fact that interruptions of female justices by male justices are associated with lower word counts for the interrupted female justices in ways that interruptions by other women are not. The results corroborate conversational and power dynamics previously explored by sociolinguists, but also extend those findings to accommodate the characteristics of more formal, high-stakes discussions involved in the creation of public policy.